2018
DOI: 10.1097/md.0000000000013896
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative lymphocyte-to-monocyte ratio (LMR) could independently predict overall survival of resectable gastric cancer patients

Abstract: Preoperational hemogram parameters have been reported to be associated with the prognosis of several types of cancers. This study aimed to investigate the prognostic value of hematological parameters in gastric cancer in a Chinese population. A total of 870 gastric cancer patients who underwent radical tumorectomy were recruited from January 2008 to December 2012. Preoperative hematological parameters were recorded and dichotomized by time-dependent receiver operating characteristic curves. The survival curves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 36 publications
(38 reference statements)
1
39
0
1
Order By: Relevance
“…PLR in 44 cohorts with 26,901 GC patients were evaluated for OS [ 7 , 11 13 , 17 , 19 27 , 29 34 , 37 , 38 , 41 51 , 53 – 61 ]. The main results of this meta-analysis are listed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…PLR in 44 cohorts with 26,901 GC patients were evaluated for OS [ 7 , 11 13 , 17 , 19 27 , 29 34 , 37 , 38 , 41 51 , 53 – 61 ]. The main results of this meta-analysis are listed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A series of studies have confirmed that pre-LMR, NLR, PLR, and SII are markers of SIR and are closely related to the survival of patients with GC. [24][25][26][27] However, researchers have not studied the changes in SIR levels in patients with GC before and after surgery and their effects on the prognosis. Previous studies have confirmed that the resection margin (R-status) is an independent predictor of OS in patients with GC.…”
Section: Discussionmentioning
confidence: 99%
“…It was the first study to evaluate the relationship of LMR and miscarriage in women with early threatened abortion. Nevertheless, the PLOS ONE bulk of literature have described that the higher LMR was a negative factor for the prognosis of diseases, such as gastric cancer [30] and early-stage Hodgkin lymphoma [31]. But a meta analysis study has suggested that the low LMR was associated with the poor outcome for patients with esophageal squamous cell carcinoma [32].…”
Section: Discussionmentioning
confidence: 99%